2010
DOI: 10.1371/journal.pone.0009429
|View full text |Cite
|
Sign up to set email alerts
|

miR-24 Regulates Apoptosis by Targeting the Open Reading Frame (ORF) Region of FAF1 in Cancer Cells

Abstract: BackgroundmicroRNAs (miRNAs) are small noncoding RNAs that regulate cognate mRNAs at the post-transcriptional stage. Several studies have shown that miRNAs modulate gene expression in mammalian cells by base pairing to complementary sites in the 3′-untranslated region (3′-UTR) of the target mRNAs.Methodology/Principal FindingsIn the present study, miR-24 was found to target fas associated factor 1(FAF1) by binding to its amino acid coding sequence (CDS) region, thereby regulating apoptosis in DU-145 cells. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 44 publications
3
151
3
2
Order By: Relevance
“…A luciferase reporter assay was employed to demonstrate the direct binding of MIR168a to exon 4 of LDLRAP1. The same strategy has been used by others in studying miRNA targeting in coding regions [30][31][32]. In this experiment, the wild-type (WT) or mutant (MUT) MIR168a complementary site (CS), WT or MUT LDLRAP1 binding site (BS), the human LDLRAP1 exon 4, and human LDLRAP1 coding sequence (CDS) were cloned into a luciferase reporter plasmid ( Figure 3G) and transfected into HepG2 cells combined with pre-MIR168a.…”
Section: Lin Zhang Et Al 113mentioning
confidence: 99%
See 1 more Smart Citation
“…A luciferase reporter assay was employed to demonstrate the direct binding of MIR168a to exon 4 of LDLRAP1. The same strategy has been used by others in studying miRNA targeting in coding regions [30][31][32]. In this experiment, the wild-type (WT) or mutant (MUT) MIR168a complementary site (CS), WT or MUT LDLRAP1 binding site (BS), the human LDLRAP1 exon 4, and human LDLRAP1 coding sequence (CDS) were cloned into a luciferase reporter plasmid ( Figure 3G) and transfected into HepG2 cells combined with pre-MIR168a.…”
Section: Lin Zhang Et Al 113mentioning
confidence: 99%
“…We found that the rate of the inhibition of luciferase activity by MIR168a was dependent on the ratio of pre-MIR168a to BS-containing luciferase reporter (Supplementary information, Figure S3A) and that the efficiency of MIR168a inhibition of LDLRAP1 expression was similar to the inhibition of target genes by endogenous miRNAs (miR-16, miR-21, and miR-150; Supplementary information, Figure S3B). To determine whether MIR168a could directly target LDLRAP1 within its CDS, we followed the strategy proposed by others [30][31][32] and created a construct that expressed the full-length ORF of LDLRAP1 ( Figure 3I). Furthermore, we used site-directed mutagenesis to create a variant of the LDLRAP1 construct in which the MIR168a target site was mutated while leaving the LDLRAP1 aminoacid sequence intact ( Figure 3I).…”
Section: Lin Zhang Et Al 113mentioning
confidence: 99%
“…Another oncogenic miRNA exerting its anti-apoptotic effects by inhibiting FasL directly is miR-21, which is found to be upregulated in advanced pancreatic cancer patients [165]. miR-24 regulates apoptosis by binding to coding sequence of Fas-associated factor 1 (FAF1) mRNA and induced apoptosis of several different types of cancer [166]. miR-21 also negatively regulates PTEN, a tumor suppressor gene, involved in the apoptotic pathway through the formation of DISC complex in many tumors such as breast and gastric cancers [167,168].…”
Section: Micrornas In Extrinsic and Intrinsic Apoptotic Pathwaysmentioning
confidence: 99%
“…In animals, miRNA target sites are located mainly in the 3'-untranslated region (3'-UTR) of target mRNAs (Chekulaeva and Filipowicz, 2009), although there are examples of target sites in the coding region (Qin et al, 2010). Until now, over 1400 miRNAs have been identified in humans.…”
Section: Introductionmentioning
confidence: 99%